VOCATIONAL HIGH SCHOOL ENGLISH TEACHERS’ VOICE OF CURRICULUM CHANGE - Dewi Sukawati; Tono Suwartono; Asti Diah Palupi (Universitas Muhammadiyah Makassar, 2023)
Teachers' attitudes toward curricular changes cause a variety of challenges regarding the implementation of school-based teaching and learning. The objective of this descriptive-qualitative research is to explore teachers' voice toward curriculum change from 2013 Curriculum to Freedom-to-Learn Curriculum at private vocational high schools. Data was gathered from two vocational high school English teachers volunteers in Banyumas City, Indonesia. They were recruited through convenience sampling. In-depth interviews and corresponding documents were used to obtain data. The interview focuses on teachers' understanding of the curricula, administration, assessment system implemented, and teachers' attitudes toward curriculum change. The results reveal that, at the time the study was carried out, the teachers understood both the 2013 Curriculum and Freedom-to-Learn Curriculum. They were able to adjust to changes in the administration procedure and the evaluation system. They agreed that it is too soon to see the effects of the newly implemented Freedom-to-Learn Curriculum by now, while believing the curriculum will find its way with a better understanding and execution over time. The researcher urges other researchers to do further investigations on this qualitative approach related to a broader issue, more general data, and more relevant methods.